Protective effects of coenzyme Q10 and L-carnitine against statin-induced pancreatic mitochondrial toxicity in rats - Melina Sadighara; Jalal Pourahamad Joktaji; Valiollah Hajhashemi; Mohsen Minaiyan (Wolters Kluwer Medknow Publications, 2017)
Statins are widely used in patients with hyperlipidemia and whom with high risk of cardiovascular diseases. Unfortunately, statins also exert some adverse effects on the liver and pancreas and enhance the risk of type 2 diabetes mellitus. The objective of the present research was to investigate the protective effects of coenzyme Q10 (Co-Q10) and L-carnitine (LC) on statins induced toxicity on pancreatic mitochondria in vivo. Seven groups of male Wistar rats received atorvastatin (20 mg/kg, p.o.), atorvastatin + Co-Q10 (10 mg/kg, i.p.), atorvastatin + LC (500 mg/kg, i.p.), lovastatin (80 mg/kg, p.o), lovastatin + Co-Q10 (10 mg/kg, i.p.), and lovastatin + LC (500 mg/kg, i.p.). Serum glucose and insulin levels were measured before and after two weeks of treatment, while the pancreas was removed and toxic effects of statins, as well as the protective effects of Co-Q10 and LC were assessed. The results showed that atorvastatin and lovastatin significantly increased glucose level and decreased insulin secretion. The glucose level in Co-Q10 and LC groups was significantly lower than statins alone groups. The findings also showed that statin groups had higher rate of pancreatic toxicity including higher level of reactive oxygen species production, decreased cytochrome c oxidase activity, collapse of mitochondrial membrane potential and swelling in comparison to controls. These factors were significantly diminished by co-administration of Co-Q10 or LC compared to statin groups alone. Additionally, supplements caused a significant increase in serum insulin and succinate dehydrogenase activity. Our study provided new evidence supporting beneficial effects of Co-Q10 and LC on statin-induced pancreatic toxicity.